Statistics in finance, operation research and forecasting - Lau, Wee Yeap (Penerbit UniMAP, 2023)
This book, Statistics in Finance, Operation Research and Forecasting, is a collection of chapters that showcase the recent topic of interest and suitable statistical techniques applied to this work. These chapters enable readers to quickly identify their interests while looking beyond the sub-theme and exploring how these studies will impact society, industry, or policymakers. In addition to the subject matter, it is known that different topics will require different statistical techniques. This technique is due to the evolution of the subject area or, sometimes, the migration of techniques from other disciplines. Readers will learn and appreciate the application of such techniques in their respective fields.